Identification and Investigation of miRNAs From Gastrodia elata Blume and Their Potential Function - Xia, Chunxin; Zhou, Huaixiang; Xu, Xiaoyuan; Jiang, Tianlong; Li, Shouliang; Wang, Dan; Nie, Zuoming; Sheng, Qing (Frontiers in Pharmacology, 2020)
Gastrodia elata (G. elata) is a valuable traditional Chinese medicine with neuroprotection, antiinflammatory and immune regulatory functions. MicroRNAs(miRNA) is a kind of endogenous noncoding small RNAs that plays distinctly important roles for gene regulation of organisms. So far, the research on G. elata is mainly focused on the pharmacological functions of the natural chemical ingredients and the function of G. elata miRNA remains unknown. In this study 5718 known miRNAs and 38 novel miRNAs were identified by high-throughput sequencing from G. elata. Based on GO and KEGG analysis, we found the human genes possibly regulated by G. elata miRNAs were related to the cell cycle, immune regulation, intercellular communication, etc. Furthermore, two novel miRNAs as Gas-miR01 and Gas-miR02 have stable and high expression in the medicinal tissue of G. elata. Further bioinformatics prediction showed that both Gas-miR01 and Gas-miR02 could target Homo sapiens A20 gene, and the Western Blotting indicated they could inhibit A20 expression in 293T cells, suggesting that G. elata-unique miRNAs might be involved in certain physiological processes. The animal experiment showed that Gas-miR01 and Gas-miR02 could be detected in some tissues of mice by intragastric administration. These results supported for the functional study of G. elata miRNAs.